Components of informatics competencies in providing nursing and midwifery electronic health services: A systematic review - Omid Ameli; Raziyeh Maasoumi; Asieh Darvish; Arezoo Rasti; Keshvar Samadaeegelehkolaee; Shadi Sabetghadam; Mohammad Javad Mansourzadeh; Saghi Ghafourian Abadi (Payesh)
Objective(s): Informatics in nursing and midwifery is developing and evolving worldwide. The present study aimed to systematically review the existing literature to identify the components of informatics competencies in the provision of electronic health services in nursing and midwifery. Methods: Web of Science, PubMed, and Scopus databases were searched using the keywords telemedicine, e-health informatics, competence, and their equivalents, without time limits. The quality of the articles was checked independently by two researchers using ten criteria selected from the Strobe checklist. Analysis was conducted in accordance with PRISMA guidelines. Results: In all 668 articles retrieved. After removing duplicates, 187 articles remained, and after reviewing the full text of the articles, 13 studies were included in the final review and analysis. Articles were on providing nursing services and no studies were found for midwifery care. In total, "e-health literacy", "nurses' attitude towards the provision of e-health services" and "individual-social-occupational factors related to informatics competence" were among the components found in studies related to nursing. Conclusion: The review indicated the need for basic knowledge, work on nurses' attitudes and research in nurses' informatics competence. Informatics competence and its related components in midwives and midwifery students were lacking in the literature, so it is recommended to investigate this among midwifery groups.